365 steps to self confidence - "Preston, David Lawrence" (Mumbai, 2006)
This book has been written for everyone - young and old, men, women, students, educators, business people, administrators, parents, homemakers, sports enthusiasts, entertainers - yes and you. It has been carefully structured into 52 sections, covering the following areas: Deciding to be confident, Self-Awareness, Thinking confidently, Using your imagination to improve self-image, Acting with confidence, Confident communication. Each section contains information, insights and words of inspiration, plus seven exercises, practical hints or points to ponder. That's one a day - not too taxing, is it?
Keywords: Self confidence